Faunal mediated carbon export from mangroves in an arid area - M.E.M. Walton (17092969) (2021)
The outwelling paradigm argues that mangrove and saltmarsh wetlands export much excess production to downstream marine systems. However, outwelling is difficult to quantify and currently 40–50% of fixed carbon is unaccounted for. Some carbon is thought outwelled through mobile fauna, including fish, which visit and feed on mangrove produce during tidal inundation or early life stages before moving offshore, yet this pathway for carbon outwelling has never been quantified. We studied faunal carbon outwelling in three arid mangroves, where sharp isotopic gradients across the boundary between mangroves and down-stream systems permitted spatial differentiation of source of carbon in animal tissue. Stable isotope analysis (C, N, S) revealed 22–56% of the tissue of tidally migrating fauna was mangrove derived. Estimated consumption rates showed that 1.4% (38 kg C ha−1 yr−1) of annual mangrove litter production was directly consumed by migratory fauna, with <1% potentially exported. We predict that the amount of faunally-outwelled carbon is likely to be highly correlated with biomass of migratory fauna. While this may vary globally, the measured migratory fauna biomass in these arid mangroves was within the range of observations for mangroves across diverse biogeographic ranges and environmental settings. Hence, this study provides a generalized prediction of the relatively weak contribution of faunal migration to carbon outwelling from mangroves and the current proposition, that the unaccounted-for 40–50% of mangrove C is exported as dissolved inorganic carbon, remains plausible. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2020.142677